Sistem Layanan Surat Pengantar Kependudukan dengan Menggunakan Telegram Bot: (Studi Kasus pada Dusun Ngipik, Desa Mayungsari, Kecamatan Bener, Kabupaten Purworejo) - Dian Adiyoko; Purwono Hendradi; Setiya Nugroho (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Ngipik Hamlet provides various types of population introduction letter services including creating birth certificates, updating family cards due to the addition of new family members, updating family cards due to the death of a family member, updating family cards due to a family member's relocation, issuing new Identity Cards for individuals turning 17 years old, updating Identity Cards due to changes in status, issuing marriage certificates, issuing certificates of insufficient financial capability, issuing business certificates, and issuing death certificates. However, these services are currently manual, resulting in inefficient processing time and the risk of document loss or incomplete documentation during the application process. Therefore, there is a need for a system that can support the application process for population introduction letters. The objective of this research is to develop a Telegram bot utilizing Google Form and Google Spreadsheet. The "Bot Layanan Surat Pengantar Kependudukan Dusun Ngipik" was tested using the black-box method, where each service was tested using dummy resident data and the required documents were inputted according to the specified requirements. The results show the status of the complete file and the evaluation of the file according to the requirements. With the existence of this "Bot Layanan Surat Pengantar Kependudukan", residents can easily submit their introduction letter requests conveniently from anywhere and at any time. This serves as an alternative solution that simplifies the process of requesting population introduction letters for residents.